Labour rationing of different farm types in Kazakhstan: A shadow price analysis - Katharina Vantomme (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
After the breakdown of the Soviet Union many socioeconomic, but also demographic changes took place in Kazakhstan. The large collective farms have partly been broken up. The result was a tri-partitioned farm structure with agricultural enterprises including agroholdings, individual farms as well as household farms. Furthermore, a strong exodus especially from northern Kazakhstan took place, which included many skilled workers, leading to a scarcity of labour and to mismatches between skills offered and skills needed in agriculture. However, the potential of the Kazakh agriculture cannot be fully tapped without suitable labour. Thus, at present low productivity prevail. Therefore, a central term of the dissertation is the term "labour rationing". An agricultural unit is labour rationing if it is not able to find enough suitable workers even though it would be willing to pay a higher wage than the real wage. This dissertation focused on investigating labour rationing in the rural areas of Kazakhstan using two cross-sectional farm level data sets from 2003 and 2011 with data collected in the two oblasts, Akmola and Almaty. Besides, the production model under factor constraint was applied. From this model the shadow price analysis was derived with help of the Lagrangian method. Three Heckman models, for 2003, 2011 as well as for 2003 and 2011 together were estimated as well as the respective shadow prices of the different farm types. The latter were then compared with the real wages. All farm types faced an excess demand for labour. However, agroholdings suffered from the strongest labour rationing and thus, had most problem finding suitable workers, skilled workers in particular. Regarding the reasons for labour rationing, the analysis suggests mainly the following: * In 2011, agricultural producers that carried out joint activity with other agricultural units were less likely to be labour rationed than those that did not carry out any joint activity together with others. * Agricultural units with a peripheral and poorly connected location were more likely to be rationed on the labour market. Moreover, in Akmola oblast labour shortages were more severe than in Almaty oblast. * Regarding the value of machinery and movable equipment, it can be said that these factors normally rather attract workers, especially in Kazakhstan. However, in order to operate more sophisticated machinery more skills are needed. But skilled workers were particularly scarce. * Regarding education it cannot be clearly observed that more educated managers have fewer problems or more problems finding workers in Kazakhstan. Finally, it can be said that according to the data wages in agriculture in Kazakhstan did rise if 2003 and 2011 are compared, but so did the shadow wages. Thus, an excess demand for labour and the problem of labour rationing persist. Nevertheless, it seems that the labour productivity increased which might be due to investments in machinery. At the same time this means that especially skilled workers are in demand. – – Nach dem Zerfall der Sowjetunion fanden in Kasachstan nicht nur viele sozioökonomische Umbrüche, sondern auch demographische Veränderungen statt. Die großen kollektiven Landwirtschaftsbetriebe wurden teilweise aufgelöst, was zu einer Koexistenz von hauptsächlich drei Organisationsformen führte, nämlich Agrarunternehmen inklusive Agroholdings, Einzelbetrieben und Hauswirtschaften. Außerdem kam es zu einem Exodus, insbesondere aus Nordkasachstan, der viele ausgebildete Arbeiter betraf, was zu Arbeitskräftemangel und einer Diskrepanz zwischen zur Verfügung stehenden Qualifikationen und benötigten Qualifikationen führte. Das Potential der kasachischen Landwirtschaft kann ohne passende Arbeitskräfte jedoch nicht vollständig ausgenutzt werden. Daher blieb die Produktivität bisher niedrig. Ein zentraler Begriff dieser Dissertation ist der Begriff der "Arbeitsrationierung". Ein Betrieb ist auf dem Arbeitsmarkt rationiert, wenn er nicht genug geeignete Arbeiter finden kann, obwohl er zu der Zahlung eines höheren Lohns als des Reallohns bereit wäre. Der Schwerpunkt der Dissertation liegt darin, Rationierung auf dem ländlichen Arbeitsmarkt in Kasachstan mithilfe von zwei Querschnittsdatensätzen auf Betriebsebene aus den Jahren 2003 und 2011, die in den Oblasten, Akmola und Almaty gesammelt wurden, zu untersuchen. Das Produktionsmodell mit Faktorbeschränkung wurde angewendet. Von diesem Modell wurde mithilfe der Lagrange-Methode die Schattenpreisanalyse abgeleitet. Drei Heckman-Modelle, für 2003, 2011 sowie 2003 und 2011 zusammen, wurden geschätzt, eine Schattenpreisanalyse wurde für die verschiedenen Betriebsformen durchgeführt. Alle Betriebsformen wiesen eine Überschussnachfrage nach Arbeitskräften auf, dennoch waren die Agroholdings am stärksten von Rationierung auf dem Arbeitsmarkt betroffen und taten sich insbesondere schwer, ausgebildete Arbeiter zu finden. Als Gründe für die Rationierung auf dem Arbeitsmarkt schlägt die Analyse hauptsächlich folgende Gründe vor: * Überbetriebliche Kooperation beeinflusste 2011 die Wahrscheinlichkeit der Rationierung auf dem Arbeitsmarkt negativ. * Geografische Faktoren, wie eine günstige Lage des Betriebes sowie eine intakte Infrastruktur vor Ort, beeinflussten die Wahrscheinlichkeit der Rationierung auf dem Arbeitsmarkt negativ. Außerdem war die Knappheit an Arbeitskräften in Akmola stärker ausgeprägt als in Almaty. * Der Wert der beweglichen Ausstattung und der Maschinen wirken eher anziehend auf Arbeitskräfte, insbesondere in Kasachstan. Dennoch wird mehr Kompetenz benötigt, um anspruchsvollere Maschinen bedienen zu können. Gleichzeitig sind gut ausgebildete Arbeiter besonders rar. * Für den Fall Kasachstan konnte anhand der Ergebnisse nicht festgestellt werden, dass gebildetere Manager mehr oder weniger Probleme hätten, Arbeitskräfte zu finden. Abschließend lässt sich sagen, dass die Löhne in der kasachischen Landwirtschaft von 2003 bis 2011 gestiegen sind. Allerdings sind dies auch die Schattenpreise. Daher bleibt das Problem einer Überschussnachfrage und einer Rationierung auf dem Arbeitsmarkt bestehen. Dennoch scheint es, dass die Arbeitsproduktivität möglicherweise durch Investitionen in Maschinen gestiegen ist. Gleichzeitig bedeutet dies, dass besonders gut ausgebildete Arbeitskräfte verstärkt nachgefragt werden.
urn:nbn:de:gbv:3:2-86093
Keywords: 330